Synthesis of Gold Nanoparticles Capped-Benzoic Acid Derivative Compounds (o-, m-, and p-Hydroxybenzoic Acid) - Agustina Sus Andreani; Eko Sri Kunarti; Sri Juari Santosa (Indonesian Journal of Chemistry, 2019)
The effect of a hydroxyl functional group of the benzoic acid derivative compound, i.e. o-hydroxybenzoic acid, m-hydroxybenzoic acid, and p-hydroxybenzoic acid on the synthesis of AuNPs has been studied. It was revealed that the pH, heating time, the concentration of capping agent and the concentration of Au3+ affected the formation of AuNPs. We discovered that o-hydroxybenzoic acid possessed the highest stability, yet it needed the highest concentration of Au3+ and faster reaction time than p-hydroxybenzoic acid and slower than m-hydroxybenzoic acid. The stability was verified by means of UV-Vis spectrophotometer, XRD, TEM, Particle Size Analyzer (PSA), and Zeta Potential with an aging time of more than 5 months. We concluded that o-hydroxybenzoic acid acquired the most effective redox reaction instead of m-hydroxybenzoic acid and p-hydroxybenzoic acid, resulted in the smaller sized and unaggregated AuNPs. We also confirmed that the hydroxyl group of o-hydroxybenzoic acid, m-hydroxybenzoic acid and p-hydroxybenzoic acid is the functional group responsible for the reduction of Au3+ to Au0.